Association of inflammatory markers with all-cause mortality and cardiovascular mortality in postmenopausal women with osteoporosis or osteopenia - Li Qu; Xiaole Zuo; Jing Yu; Ran Duan; Botao Zhao (BMC, 2023)
Abstract Background The objective of the present study was to investigate whether associations exist between inflammatory biomarkers and all-cause mortality and cardiovascular disease (CVD) mortality in women with postmenopausal osteoporosis (PMOP) or osteopenia. Methods In this retrospective cohort study, data were obtained from the National Health and Nutrition Examination Survey database from the years 2007 to 2010, 2013 to 2014, and 2017 to 2018. The inflammatory biomarkers including neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), neutrophil × platelet/lymphocyte (SII), neutrophil × monocyte/lymphocyte (SIRI), and neutrophil × monocyte × platelet/lymphocyte ratio (AISI) were calculated. Results A total of 2,834 women were included, with a median survival of 113.51 (3.15) months. During follow-up, 602 women died of all-cause mortality and 185 women died of CVD. NLR, MLR, SIRI, and AISI were significantly associated with all-cause mortality in postmenopausal women with osteoporosis or osteopenia. NLR, MLR, SIRI, and AISI were related to CVD mortality in postmenopausal women with osteoporosis or osteopenia (All P < 0.05). Based on the results of the subgroup analysis, AISI, SIRI, and MLR were associated with all-cause mortality and CVD mortality in postmenopausal women with PMOP or osteopenia who had a history of CVD and diabetes. AISI, SII, MLR, and NLR were associated with all-cause mortality and CVD mortality in PMOP or osteopenia women with a body mass index (BMI) > 25 kg/m2. PLR was associated with all-cause mortality in PMOP or osteopenia women aged ≥ 65 years. Conclusion Inflammatory biomarkers were correlated with mortality risk in the PMOP or osteopenia population. This finding may be helpful for the prognosis management of PMOP or osteopenia in postmenopausal women.